(untitled) (Socio-economic relations in the digital society, 2019)
This article is devoted to studying the impact of technological development on banking customers servicing. The development of the information and communications technologies stimulates the innovations’ raising and in the financial sphere it is one of the relative importance. Thought the innovations are felt as a inevitable process that has being changed our world there are still two diff erent approaches to the bank distribution activity. The first is a conservative one that insists on the traditional face-to-face servicing and any innovative distribution systems are thought not to be of the vital importance, but just an addition. In contrast, the adherents of the second approach perceive the innovations’ implementation is the only way for banks existence in the future. We completely agree with the second approach and in this essay it’s revealed the foreign experience of the individualization process of the bank’s sales. It’s grounded the necessity of the substantiation of the channel service efficiency in accordance with the content of the fi nancial product, customer’s type and stage of the sales process of the certain fi nancial service.